33=-3f

Simple and best practice solution for 33=-3f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 33=-3f equation:


Simplifying
33 = -3f

Solving
33 = -3f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '3f' to each side of the equation.
33 + 3f = -3f + 3f

Combine like terms: -3f + 3f = 0
33 + 3f = 0

Add '-33' to each side of the equation.
33 + -33 + 3f = 0 + -33

Combine like terms: 33 + -33 = 0
0 + 3f = 0 + -33
3f = 0 + -33

Combine like terms: 0 + -33 = -33
3f = -33

Divide each side by '3'.
f = -11

Simplifying
f = -11

See similar equations:

| 2.5d+3.25=1+3.25 | | -7-13=9x+18-18x | | -70=7k | | 0=4/15y-28 | | 1/x=7/3 | | 7-8d=39 | | 1.08y=y+48 | | 3x-55+2x=5y | | Y+4.7=-8.6-5.3 | | -4x+6-5(x-1)=-(3x-3)-5x+5 | | X-0.2=6.4 | | 5x-2(3-4x)=3(x-3)-57 | | (4f^2-3)+11f=0 | | 5x+18+3x+34=90 | | y-7=-2.66(x-10) | | 42y+16= | | 4(2x+2)+5=3+2(4x+5) | | Z-2.8=10.9 | | Y/0.2=0.8 | | 16a^2+24ab+9b=(a+3b) | | (8x-8)/7=-8 | | y-7=0.66(x-10) | | 8=2v | | 2-(2x+3)=-11 | | 6x+5=5x+11 | | 0.5a=1.5 | | 3y-8+y+56=6y+50-4y | | (-3/4)²x | | 0.09xX=78.73 | | 12x+5=8x-17 | | 3m+5m=10 | | (-3/4)²*x |

Equations solver categories